Analisa Faktor Yang Mempengaruhi Kinerja Keuangan Perusahaaan Barang Sektor Konsumen Non-Primer IDX-IC Periode 2019- 2021 - Pangestu, Juan Carlos; Margaretha, Phebyana (Owner : Riset dan Jurnal Akuntansi, 2024)
Business development continues to increase from year to year in Indonesia due to technological developments, changes in market share and changes in sales models due to the pandemic in 2019. The company's financial performance is used to measure the level of success in running a business to make a profit. Every company strives to continuously improve its company's performance in order to generate profits and be able to survive in the midst of changing times. This study aims to examine the effect of leverage, liquidity, company size, asset structure and Working Capital Turnover on financial performance in companies in the Non-Primary Consumer Idx-Ic sector for the 2019-2021 period. Sampling was carried out using a purposive sampling technique. This type of research uses descriptive statistical tests and multiple linear regression methods. The object of this study is the financial statements of the Non-Primary Consumers sector Idx-Ic for the period 2019-2021. The results of the study show that the five independent variables above which are used to see the effect on financial performance have an influence and the research model is feasible to use.